Between containment and crackdown in Geylang, Singapore: Urban crime control as the statecrafting of migrant exclusion. (September 2022) - Greener, Joe; Naegler, Laura
Based on a case study conducted in Geylang, Singapore, this article explores the role of urban policing, surveillance and crime control as mechanisms of social ordering that contribute to the marginalisation of excluded groups, including low-income migrant workers and sex workers. Adopting a statecraft approach that emphasises the significance of 'governing through crime' for the upholding of urban political-economic projects, we examine the entanglement of political discourses and crime and social control practices as co-constructive of class- and race-based inequality in Singapore. Drawing from qualitative interviews with NGO workers and sex workers, augmented by extensive non-participant observations, we identify three processes through which state power is vectored in Geylang: the stigmatisation of the neighbourhood through association with marginalised groups, legitimising intense spatialised intervention; the enacting of performative zero-tolerance policing ; and the containment and surveillance of illicit activities within the neighbourhood. Contributing to discussions that advance the statecraft approach to researching urban crime control, the article shows that seemingly contradictory practices of tolerance and intervention constitute strategies of governance. The article argues that spatially specific crime control practices in Geylang generated an exclusionary 'spectacle' which symbolically connects low-income migrant workers with deviance, in turn supporting citizenship exclusion, racialised marginality and a wider politics of capital accumulation resting on disempowered labour. As we argue, crime control policies are an important form of statecraft legitimising an urban political economy that is heavily reliant on low-cost labour provided by migrant workers.